Value of schizophrenia treatment I: The patient journey - Mohr, Pavel; Galderisi, Silvana; Boyer, Patrice; Wasserman, Danuta; Arteel, Paul; Ieven, Aagje; Karkkainen, Hilkka; Pereira, Eulalia; Guldemond, Nick; Winkler, Petr; Gaebel, Wolfgang (European psychiatry, 2018)
BACKGROUND: The aim of the European Brain Council project "The Value of Treatment" was to provide evidence-based, cost-effective policy recommendations for a patient-centered and sustainable coordinated care model for brain disorders. The first part of schizophrenia study examined the needs and gaps in the patients' care pathway. METHODS: Descriptive analysis was based on an inventory of needs and treatment opportunities, using focus group sessions, expert interviews, users' input, and literature review. Three patient pathways were selected: indicated prevention, duration of untreated psychosis, and relapse prevention. RESULTS: The analysis identified several critical barriers to optimal treatment. Available health care services often miss or delay detection of symptoms and diagnosis in at-risk individuals. There is a lack of illness awareness among patients, families, and the public; scarcity of information, training and education among primary care providers; stigmatizing beliefs. Early symptom recognition and timely intervention result in better outcome and prognosis; effective management leads to a functional recovery. In the current model of care, there is insufficient cooperation between health and social care providers, patients and families, inadequate utilization of pharmacological and psychosocial interventions, lacking patient monitoring, and low implementation of integrated community care. CONCLUSIONS: Early detection and early intervention programs, timely intervention, and relapse prevention are essential for effective management of schizophrenia. It requires a paradigm shift from symptom control, achieving and maintaining remission, to the emphasis on recovery. Since the current services are not able to accomplish this goal, changes in mental health policies are needed.
Keywords: Treatment; Mental health; Recovery; Health Services Accessibility; služby péče o duševní zdraví; Patient journey; dostupnost zdravotnických služeb; Mental Health Services; lidé; psychotické poruchy; schizofrenie; prognóza; časná diagnóza; sekundární prevence; Secondary Prevention; Prevention; medicína založená na důkazech; Psychotic Disorders; Schizophrenia; Early Diagnosis; Prognosis; Evidence-Based Medicine; Humans